Russian Federation : Report on the Observance of Standards and Codes-Basel Core Principles for Effective Banking Supervision. (IMF Staff Country Reports; Country Report ;, 2016)
This paper presents an assessment of the level of implementation of Basel Core Principles for Effective Banking Supervision in Russian Federation. The legal framework currently in place provides the Central Bank of the Russian Federation (CBR) with necessary powers and responsibilities. The Russian licensing regime for banks appears exhaustive. The legal and regulatory framework provides CBR with a set of instruments and tools to ensure that the licensing process is sound. CBR also has the power to review, reject, and impose prudential conditions on any proposals to transfer significant ownership or controlling interests held directly or indirectly in existing banks to other parties. However, the legal regime for major acquisitions in Russia is found to be weak.